Preparation, characterization and utilization of coreshell super paramagnetic iron oxide nanoparticles for curcumin delivery. - C Justin; Antony V Samrot; Durga Sruthi P; Chamarthy Sai Sahithya; Karanam Sai Bhavya; C Saipriya (PLoS ONE)
In this study, super paramagnetic iron oxide nanoparticles (SPIONs) were produced by chemical co-precipitation method, then it was constructed to be a core shell nanoparticle by functionalizing with SDS, loading with curcumin and coating with a biopolymer i.e. chitosan. Each step was analyzed microscopically and spectroscopically. The produced coreshell particles were between 40 and 45nm and these coreshell particles were utilized for drug delivery studies against cervical cancer cell line-HeLa cells. The coreshell SPIONs were found to be releasing curcumin in between 6 and 12 h, which was evidenced by increased apoptotic cells and increased caspase 3 expression in HeLa cells.